Threatened species in a threatened ecosystem: the conservation status of four Solanum species in the face of ongoing habitat loss. Issue 3 (20th May 2019) - Fensham, Roderick J.; Halford, Jason; Hansen, Chris; Laffineur, Boris; Williams, Billie
Abstract: Plant biodiversity is threatened by habitat loss, fragmentation and invasion by exotic species, but the effects of these disturbances on individual plant species are rarely quantified. Since the 1950s, brigalow Acacia harpophylla forests in Australia have been extensively cleared and converted to pastures dominated by exotic grasses. Here we assess the habitat requirements, population numbers and threats for four poorly known bush tomato species, Solanum adenophorum, Solanum dissectum, Solanum elachophyllum and Solanum johnsonianum . Herbarium records and surveys demonstrated a strong association of all four species with brigalow habitat, although S. elachophyllum also occurred in other habitat. We derived historical and current population estimates from plant densities at current sites and the area of mapped brigalow habitat. Density estimates are imprecise because the survey data vary greatly, but the assessment indicates the populations of all four species have declined > 93%. Solanum dissectum and S. johnsonianum did not persist in cleared brigalow habitat, whereas S. adenophorum and S. elachophyllum had some capacity to persist in clearings. None of the species occur where the exotic grass cover is > 40%. Between 27% and 57% of the records of the four species are in brigalow remnants with a high edge-to-area ratio or open canopy (< 50% cover), making them highly vulnerable to invasive grasses. We recommend the categorization of S. dissectum and S. johnsonianum as Critically Endangered, S. adenophorum as Vulnerable and S. elachophyllum as Near Threatened.